Bulk sediment geochemistry from XRF-scanning of sediment core POS457_889-1 - Dirk Nürnberg; Nadine Gehre; Sebastian Fessler; Maryam Mirzaloo (PANGAEA, 2025)
R/V POSEIDON cruise POS457 aimed at sediment coring on the Iceland-Faroe Ridge, the shelf and slope areas south of Iceland, and on Reykjanes Ridge in order to reveal paleoceanographic and paleoclimatic information. Gravity corer 889-1 was recovered from southeast of Reykjanes Ridge close to Iceland (N Atlantic, 63°03.04 extquotesingleN 23°23.19 extquotesingleW, 923.0 m water depth). We present radiocarbon datings and high-resolution XRF-scanner element compositions of bulk sediments. In addition, we provide benthic and planktic stable oxygen and carbon isotopes, as well as planktic foraminiferal element ratios.